Analytical and Monte Carlo approaches to evaluate probability distributions of interruption duration - da Silva, AML; Schmitt, W. F.; Cassula, A. M.; Sacramento, C. E. (Institute of Electrical and Electronics Engineers (IEEE), 2005)
Regulatory authorities in many countries, in order to maintain an acceptable balance between appropriate customer service qualities and costs, are introducing a performance-based regulation. These regulations impose penalties-and, in some cases, rewards-that introduce a component of financial risk to an electric power utility due to the uncertainty associated with preserving a specific level of system reliability. In Brazil, for instance, one of the reliability indices receiving special attention by the utilities is the maximum continuous interruption duration (MCID) per customer.This parameter is responsible for the majority of penalties in many electric distribution utilities. This paper describes analytical and Monte Carlo simulation approaches to evaluate probability distributions of interruption duration indices. More emphasis will be given to the development of an analytical method to assess the probability distribution associated with the parameter MCID and the correspond ng penalties. Case studies on a simple distribution network and on a real Brazilian distribution system are presented and discussed.
Keywords: distribution reliability; Markov chains; Monte Carlo simulation; reliability network analysis